PERFORMANCE of MOBILE LEARNING on GPRS NETWORK - LINAWATI, LINAWATI (Majalah Ilmiah Teknologi Elektro; Vol 11 No 1 (2012): (January - June) Majalah Ilmiah Teknologi Elektro, 2013)
Mobile learning becomes new life style in modern era. In view of the fact that mobile phone turns into basic need of people. However most people live in rural area only affords cell phones with General Packet Radio Service GPRS facilities. Yet telecommunication infrastructure in rural area does not support 3G facilities. Therefore the paper investigates performance of mobile learning in GPRS network. The purpose of the paper is to enlarge e-learning facilities to people with GPRS facilities. Overall the paper shows that good performance of mobile learning in GPRS network. The results present excellent packet loss and good delay. However throughput is slightly poor.
Keywords: Mobile learning. GPRS, 3G